Perilymphatic fistula with characteristic findings of the inner ear by contrast-enhanced magnetic resonance imaging: a case report - Ito, Yusuke; Seo, Toru; Sasano, Yoshiyuki; Mochizuki, Fumihiro; Koizuka, Izumi (Frontiers in Neurology, 2023)
A perilymphatic fistula (PLF) presents with abnormal traffic in the otic capsule, causing cochlear and vestibular symptoms. However, the mechanisms underlying symptom recurrence remain controversial. Herein, we report the case of a 27-year-old female who complained of hearing disturbance in her right ear and recurrent vertigo after sudden onset of hearing loss with vertigo. The caloric test revealed unilateral weakness in the right ear, and the video head impulse test (vHIT) showed decreased vestibulo-ocular reflex (VOR) gain. Contrast-enhanced magnetic resonance imaging (MRI) using hybrid of reversed image of positive endolymph signal and negative image of perilymph signal (HYDROPS) indicated a collapsed endolymphatic space. As the vestibular symptoms did not improve, an exploratory tympanotomy was performed on the right ear. Although perilymph leakage was not noted in the oval or round windows, both windows were sealed with connective tissue. The patient's vestibular symptoms rapidly improved after surgery, and postoperative contrast-enhanced MRI showed improvement in the collapsed endolymphatic space. Although the caloric test revealed unilateral weakness, the VOR gain on the vHIT improved to normal on the right side. Thus, these findings indicated that recurrent symptoms caused by PLF are associated with a collapsed endolymphatic space. We speculate that the collapsed endolymphatic space was due to a ruptured Reissner's membrane. We hypothesized that sealing the fistula would promote normalization of perilymph pressure. The ruptured Reissner's membrane may have been gradually repaired as vestibular symptoms improved. This case adds to the existing literature on the occurrence of the “double-membrane break syndrome”. Collapse of the endolymph due to a ruptured Reissner's membrane may be the cause of PLF symptoms.